Method for coding positional coordinates of a frame-spline tensor in a mixed poliadic space - Пархоменко, Максим Володимирович (Science-based technologies, 2020)
The need to improve the efficiency of the provision of video services for information support systems for the functioning of critical infrastructure facilities, including under conditions of information and cyber attacks from an opposing or competing side, is emphasized. Especially the research problem concerns the delivery of high-resolution dynamic video information resources using mobile infocommunication technologies, both ground-based and aerospace-based. The necessity of increasing the efficiency of the compact syntactic representation of the sequence of B-P frames for information technologies, process and transfer of dynamic video resources is substantiated. The advantages of the approach with respect to coding a sequence of frames of B-P types based on the construction of structural splines and their corresponding frame structures for differentiated blocks of frames in the transformable space are shown. To increase the amount of redundancy that can be potentially eliminated, it is proposed to form a set of frame splines for a dynamic sequence of TD-blocks. In this case, the statistical, psycho-visual and structural redundancy of the video sequence is reduced on the basis of identifying the corresponding patterns, both within frames and between them. The main technological approaches to the creation of a method for efficient coding of positional coordinates of single-element frame-spline tensors of a sequence of B-P frames on the basis of a two-pole mixed poliadic representation are revealed. It is shown that the integration of the created method for encoding a dynamic sequence of predicted video frames into the information technology for processing and transmitting video resources allows to increase its functioning efficiency in terms of such indicators as time delays for bringing video information, the integrity of the video information resource. Therefore, the quality of information support for the functioning of critical infrastructure systems is improved. that the integration of the created method for coding a dynamic sequence of predicted video frames into the information technology for processing and transmitting video resources allows to increase its efficiency in terms of such indicators as time delays for bringing video information, the integrity of the video information resource. Therefore, the quality of information support for the functioning of critical infrastructure systems is improved. that the integration of the created method for encoding a dynamic sequence of predicted video frames into the information technology for processing and transmitting video resources makes it possible to increase its efficiency in terms of such indicators as time delays for bringing video information, the integrity of the video information resource. Therefore, the quality of information support for the functioning of critical infrastructure systems is improved